2006
DOI: 10.1161/01.hyp.0000208840.30778.00
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Matrix Metalloproteinase 2 Ameliorates Myocardial Remodeling in Mice With Chronic Pressure Overload

Abstract: Abstract-Matrix metalloproteinases (MMPs) play an important role in the extracellular matrix remodeling. Experimental and clinical studies have demonstrated that MMP 2 and 9 are upregulated in the dilated failing hearts and involved in the development and progression of myocardial remodeling. However, little is known about the role of MMPs in mediating adverse myocardial remodeling in response to chronic pressure overload (PO). We, thus, hypothesized that selective disruption of the MMP 2 gene could ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 32 publications
10
103
2
6
Order By: Relevance
“…However, the results were inconsistent and appeared to depend on the animal model used. Chronic pressure overload in MMP-2-deficient mice is associated with reduced cardiac interstitial fibrosis and MMP-2 transgenic mice have been reported to be associated with increased replacement fibrosis and perivascular fibrosis (25,26). The results of the present study support the theory that the degenerative activity of MMP-2 is markedly impaired in the fibrotic myocardium.…”
Section: Discussionsupporting
confidence: 83%
“…However, the results were inconsistent and appeared to depend on the animal model used. Chronic pressure overload in MMP-2-deficient mice is associated with reduced cardiac interstitial fibrosis and MMP-2 transgenic mice have been reported to be associated with increased replacement fibrosis and perivascular fibrosis (25,26). The results of the present study support the theory that the degenerative activity of MMP-2 is markedly impaired in the fibrotic myocardium.…”
Section: Discussionsupporting
confidence: 83%
“…Another possible mechanism is the contribution of myocardial MMP-2 expression in this model, since it has been reported that MMP activation plays an important role in the pathophysiology of LV remodeling (27,28) and, moreover, since myocardial MMPs can be activated by Ang II (29). Based on these findings, the activation of the renin-angiotensin system might contribute to the activation of MMP-2 and thus to the development of LV remodeling in the diabetic heart.…”
Section: Discussionmentioning
confidence: 71%
“…29 In this respect, transgenic models have contributed to the understanding of the roles for MMPs in LVH, and MMP-2 knockout mice present interesting reductions in LVH and its complications in models of heart hypertrophy. 30 These mice have increased TIMP-4 levels in the heart, and TIMP-4 is a major MMPs inhibitor. 31 Whether the reduced LVH seen in these animals is because of lack of MMP-2 activity or to the inhibitory effects of TIMP-4 on various MMPs is not known.…”
Section: Discussionmentioning
confidence: 99%